Asociaciones entre las características reproductivas y la abundancia en Gymnocalycium quehlianum (Cactaceae) a lo largo de un gradiente altitudinal - Martino, Pamela Ayelén (2021)
Even though species can have wide altitudinal ranges, little is known about how their abundance varies in these gradients and the variables associated with this variation. Hypothesis: There will be an association between abundance and reproductive characteristics, such as seed weight, germination, and the size and shape of seedlings along an altitude gradient. Study species: Gymnocalycium quehlianum Study site and date: Sierras Chicas, Córdoba Province, Argentina. 2015-2016. Methods: The density and its population structure (size classes) were measured in three sites of G. quehlianum distribution along an altitude gradient, at 615, 948, and 1,257 m asl Seeds were weighted, the percentage and germination speed were evaluated, and the length and diameter of the seedlings were measured. Results: The weight of the seed was lower in the population at intermediate altitude, while the percentage and mean germination time did not vary significantly between altitudes. The seedling size was smaller in the intermediate population while the seedlings shape of the extreme populations presented a more elongated shape. Conclusions: There is no relationship between the population abundance along the altitudinal gradient and the variables analyzed. Some variables did not show differences along the gradient, such as the germination percentage and the mean germination time, while other variables such as seed mass and the shape and size of the seedlings did contrary to expectations.